Virtual Standardized Patients Versus Traditional Academic Training for Improving Clinical Competence Among Traditional Chinese Medicine Students: Prospective Randomized Controlled Trial - Han Yang; Xiang Xiao; Xuanyu Wu; Xiaoxu Fu; Quanyu Du; Yan Luo; Bin Li; Jinhao Zeng; Yi Zhang (JMIR Publications, 2023)
BackgroundThe practical training course of internal medicine of traditional Chinese medicine (PTC-IMTCM) is primarily based on traditional case teaching, which can be stressful for teachers. The use of virtual standardized patient (VSP) applications could be an alternative; however, there is limited evidence regarding their feasibility and effectiveness. ObjectiveThis study aimed to build a VSP-TCM application according to the characteristics of PTC-IMTCM and the needs of students and to compare its efficacy with that of traditional teaching in improving TCM clinical competence among students. MethodsA prequestionnaire investigation was conducted before the course, and a VSP-TCM system was developed based on the results of the questionnaire. A randomized controlled trial was then conducted between February 26, 2020, and August 20, 2021. A total of 84 medical students were included and were divided into 2 groups: an observation group, trained with VSP-TCM (n=42, 50%), and a control group, trained with traditional academic training (n=42, 50%). Formative and summative assessments were conducted to evaluate teaching effectiveness. After completing the course, the students were administered a questionnaire to self-assess their satisfaction with the course. A questionnaire was also administered to 15 teachers to uncover their perspectives on VSP-TCM. ResultsAll participants completed the study. In the formative assessment, the VSP-TCM group performed better in medical interviewing ability (mean 7.19, SD 0.63, vs mean 6.83, SD 0.81; P=.04), clinical judgment (mean 6.48, SD 0.98, vs mean 5.86, SD 1.04; P=.006), and comprehensive ability (mean 6.71, SD 0.59, vs mean 6.40, SD 0.58; P=.02) than the control group. Similarly, in the summative evaluation, the VSP-TCM group performed better in the online systematic knowledge test (OSKT; mean 86.62, SD 2.71, vs mean 85.38, SD 2.62; P=.046), application of TCM technology (mean 87.86, SD 3.04, vs mean 86.19, SD 3.08; P=.02), TCM syndrome differentiation and therapeutic regimen (mean 90.93, SD 2.42, vs mean 89.60, SD 2.86; P=.03), and communication skills (mean 90.67, SD 4.52, vs mean 88.24, SD 4.56; P=.02) than the control group. There was no significant difference in medical writing between both groups (mean 75.07, SD 3.61, vs mean 75.71, SD 2.86; P=.37). The postcourse feedback questionnaire indicated that VSP-TCM can better enhance students' TCM thinking ability (n=39, 93%, vs n=37, 88%; P=.002), medical history collection (n=38, 90%, vs n=30, 72; P=.001), syndrome differentiation and treatment and critical thinking (n=38, 90%, vs n=37, 88%; P=.046), comprehensive clinical application ability (n=40, 95%, vs n=36, 86%; P=.009), interpersonal communication skills (n=36, 86%, vs n=28, 67%; P=.01), and autonomous learning ability (n=37, 88%, vs n=28, 67%; P=.01) than traditional academic training. Similarly, the teachers held a positive perspective on VSP-TCM. ConclusionsVSP-TCM enhances students' TCM clinical competence and dialectical thinking and improves their ability to work autonomously. Moreover, the VSP-TCM system is feasible, practical, and cost-effective and thus merits further promotion in TCM education.